El Niño - Understanding the World’s Most Powerful Climate Phenomenon - Shivani, Kupirala Sai; Joseph, B. (Chronicle of Bioresource Management, 2026)
El Niño, the most powerful interannual climate phenomenon, arises from warming of sea surface temperatures in the central and eastern Pacific, disrupting trade winds and atmospheric circulation through the Bjerknes feedback. This reorganisation of global weather leads to weakened monsoons and droughts in South Asia, floods in South America, bushfires in Australia, and altered storm tracks in Europe and North America. Historically, El Niño has caused devastating famines, notably the Great Famine of 1876–78 in India, with Telangana at its epicentre. Subsequent strong events in 1982–83, 1997–98, 2002, 2009, 2015–16, and 2023 repeatedly reduced crop yields and triggered food inflation. Forecasts for 2026 indicate belownormal monsoon rainfall, threatening kharif crops and rural livelihoods. Climate change intensifies El Niño’s severity, compounding risks to food security. Preparedness measures and agronomic strategies such as droughttolerant varieties, contingency planning, conservation agriculture, and microirrigation are essential to safeguard agriculture and livelihoods.